The perceptual learning of time-compressed speech: A comparison of training protocols with different levels of difficulty. - Yafit Gabay; Avi Karni; Karen Banai (PLoS ONE, 2017)
Speech perception can improve substantially with practice (perceptual learning) even in adults. Here we compared the effects of four training protocols that differed in whether and how task difficulty was changed during a training session, in terms of the gains attained and the ability to apply (transfer) these gains to previously un-encountered items (tokens) and to different talkers. Participants trained in judging the semantic plausibility of sentences presented as time-compressed speech and were tested on their ability to reproduce, in writing, the target sentences; trail-by-trial feedback was afforded in all training conditions. In two conditions task difficulty (low or high compression) was kept constant throughout the training session, whereas in the other two conditions task difficulty was changed in an adaptive manner (incrementally from easy to difficult, or using a staircase procedure). Compared to a control group (no training), all four protocols resulted in significant post-training improvement in the ability to reproduce the trained sentences accurately. However, training in the constant-high-compression protocol elicited the smallest gains in deciphering and reproducing trained items and in reproducing novel, untrained, items after training. Overall, these results suggest that training procedures that start off with relatively little signal distortion ("easy" items, not far removed from standard speech) may be advantageous compared to conditions wherein severe distortions are presented to participants from the very beginning of the training session.